2013
DOI: 10.1167/iovs.13-11925
|View full text |Cite
|
Sign up to set email alerts
|

Haplogroup Heterogeneity of LHON Patients Carrying the m.14484T>C Mutation in India

Abstract: Contrary to earlier reports showing preferential association of the m.14484T>C mutation with western Eurasian haplogroup J and increased clinical penetrance when present in J1 subhaplogroup background, the present study shows that m.14484T>C arose independently in a different mtDNA haplogroup and ethnic background in India, which may influence the clinical expression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
3
16
2
Order By: Relevance
“…In the present study, the frequency of m.11778G>A was 29.22% (64/219), which is much higher than previous reports of the m.14484T>C mutation (4.2%). 26 In accordance with the earlier reports, sex bias and heteroplasmy were strong factors associated with visual loss in Indian LHON with males 3.9 times more at risk of developing blindness than females. In the present cohort, at least one individual heteroplasmic for the m.11778G>A mutation was identified in 20.3% of the families, whereas no heteroplasmy was observed in our previous study of families harboring the m.14484T>C mutation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, the frequency of m.11778G>A was 29.22% (64/219), which is much higher than previous reports of the m.14484T>C mutation (4.2%). 26 In accordance with the earlier reports, sex bias and heteroplasmy were strong factors associated with visual loss in Indian LHON with males 3.9 times more at risk of developing blindness than females. In the present cohort, at least one individual heteroplasmic for the m.11778G>A mutation was identified in 20.3% of the families, whereas no heteroplasmy was observed in our previous study of families harboring the m.14484T>C mutation.…”
Section: Discussionsupporting
confidence: 89%
“…In the present cohort, at least one individual heteroplasmic for the m.11778G>A mutation was identified in 20.3% of the families, whereas no heteroplasmy was observed in our previous study of families harboring the m.14484T>C mutation. 26 The heteroplasmic families showed a 0.39-fold reduced risk of visual failure compared to families with the homoplasmic mutation. In the present study, 19 (29.7%) of 64 LHON probands with the m.11778G>A mutation experienced childhood (<18 years) age of onset.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another interesting link involving India, Saudi Arabia and the Mauritius Island is the case of the haplogroup M81. It was first detected as a sole sequence in a LHON patient from India [84]. The Saudi Ar567 sample shares 215, 4254, 6620, 13590, 16129 and 16311 substitutions with this Indian sequence and, in addition it shares substitutions 151, 6170, 7954 and 16263 with a complete sequence from the Mauritius Island [85].…”
Section: Resultsmentioning
confidence: 99%
“…Among 127 patients from three renowned centers, 8 LHON patients had the m. 14484T>C mutation accounting for 4.2% of the cases compared with 10% seen in European and Chinese patients. [3] In another Indian study, G3460A and G11778A in the mitochondrial genes MTND1 and MTND4 were found in one family each. [4]…”
mentioning
confidence: 99%